Landscape, population structure and genetic diversity of Stomoxys calcitrans - Dsouli Aymes N.; Mavoungou J.F.; De Stordeur E.; Duvallet G. (Parasite, 2009)
To investigate whether different landscapes could affect genetic diversity and structure of the cosmopolitan diptera Stomoxys calcitrans, populations from Gabon and southern France were studied using dominant amplified fragment length polymorphism (AFLP) markers. Gabon is characterized by a forested closed landscape, and southern France by an open Mediterranean landscape. The genetic diversity between Gabon and France populations did not differ significantly (P > 0.05). Contrary to our expectation, this study shows a moderate level of genetic differentiation between these two distant countries (Fst = 0.0979) and a low genetic structure among Gabonese and French populations (Fst = 0.0291 and 0.0275 respectively). This result could indicate the capacities of S. calcitrans populations to sustain a high level of gene flow, despite geographic distance and isolation.